A MARINE ANNELID AS A TREATMENT ALTERNATIVE FOR COVID-19 - Herrera-Perez, Melissa (2020)
Th e world is facing a pandemic caused by the viral infection of the SARS coronavirus- CoV-2 that triggers the COVID-19 disease. Currently, no specifi c treatment or vaccine is known to counteract the symptoms and conditions caused by the virus, but antiviral, anti-infl ammatory, immunomodulatory, mechanical support treatment, hematic, and others are being administered based on multi-organ dysfunction. When facing a new virus, the treatments used have been combined, which have generated secondary clinical eff ects in the patient. Th is study will focus on the hematic mechanical support treatment, where the patient is in a state of oxygen defi ciency. During this phase of development of the disease that the extracellular hemoglobin extracted from Arenicola marina (Linnaeus, 1758) can be an alternative treatment through a blood transplant, as it can transport up to 40 times more oxygen when compared to hemoglobin in human. According to studies, extracellular hemoglobin has a natural antioxidant that does not induce mutagenic responses, immunogenic or allergenic, granting high affi nity and cooperativity in bonding with oxygen, high structural stability, and high resistance to oxidation of the heme group, unlike human hemoglobin. Th e result of these promising investigations of scientifi ctechnological development allowed to name this new molecule, as HM-101, which has been purifi ed and used for the production of HEMOXYCarrier (HC, Hemarina SA, France), oxygen carrier for therapeutic purposes. Th is document was prepared through a bibliographic search in PubMed and Google Scholar using the following words: coronavirus, COVID-19, or SARS-CoV-2, A. marina and treatment, treatment or therapy. Th erefore, it is intended to inform about the technological scientifi c knowledge of extracellular hemoglobin extracted from A. marina as an alternative treatment for COVID-19, with promising clinical trials as a possible substitute for human hemoglobin. Likewise, the potential of scientifi c-technological research in diff erent study areas with "polychaete" annelids, based on basic research in Peru.